New Strategies for N-Heterocyclic Carbenes Catalyzed Annulations - Chen, Xiangyu (Springer Singapore : Imprint: Springer, 2017)
This thesis focuses on NHC-catalyzed annulation of nitroalkenes, enals and α,β-unsaturated carboxylic acids. (1) NHCs were found to be efficient catalysts for the [4+2] annulation of β-substituted nitroalkenes. The scope of Rauhut-Currier reaction was successfully extended to the most challenging β-substituted alkenes by this method; (2) Enals were successfully used for [4+2] annulations with azodicarboxylates catalyzed by NHC via γ-addition. Highly enantiopure tetrahydropyridazinones and γ-amino acid derivatives could be easily prepared by subsequent transformations of the resulting dihydropyridazinones. (4) The readily available α,β-unsaturated carboxylic acids were first successfully employed to generate the α,β-unsaturated acyl azolium intermediates by using NHC for the enantioselective [3+2] and [3+3] annulations.
Keywords: Chemistry.; Organic chemistry.; Medicinal chemistry.; Catalysis.; elektronické knihy; electronic books